Factors that Lead Amazon.com to A Successful Online Shopping Platform - Uma Warrier; Padmalini Singh; Chuah Wei Jien; Daisy Mui Hung Kee; Goi Zi Yi; Tan Woei Jiann; Tan Yong Liang; Gopika SB; Suji Nair; Rajesh Kumar Nair; Swapnil Digambar Lokhande; Varsha Ganatra (International Journal of Tourism and Hospitality in Asia Pasific, 2021)
The online shopping method has replaced the traditional shopping method. Amazon.com as one of the largest online shopping platforms has adopted a number of strategies which has contributed to its success. It includes innovation, outstanding customer service, execution, and diversification. The purpose of this study is to investigate the factors that lead Amazon.com to be a successful online shopping platform. This study explored what made Amazon today by gauging some factors such as the level of customer awareness, sources of awareness, customer perception, customer satisfaction, competitor analysis, competitive advantage, etc. It also investigates the opportunity Amazon gained in the market. This study proves there is a positive relationship between the factors and the success of Amazon.com.